Ecological improvement assessment of a passive remediation technology for acid mine drainage: Water quality biomonitoring using bivalves. (March 2019) - Bonnail, Estefanía; Macías, Francisco; Osta, Victoria
Abstract: A passive treatment plant, located in the Iberian Pyrite Belt (Huelva, Southwest Spain), was designed for acid mine drainage remediation. Since its installation, the improvement of water quality in terms of hydrochemical composition has been demonstrated successfully. However, according to the Water Framework Directive, the treated effluent must have ecological values for potential living. The freshwater clam Corbicula fluminea was chosen to carry out bioassessments (survival, biomarker responses, and metal bioaccumulation in soft tissue) with effluents from the mining site, as well as, products from the passive treatment plant in order to determine the level of quality of that water from the biological point of view in toxicity tests. Results discarded mortality as endpoint for biomonitoring purposes. Only the lipid peroxidation of the cell membrane evidenced significant responses, even in correlation with the pollution degree of each effluent. Regarding bioaccumulation, some elements displayed a strong relationship (Fe, Cu, Co, and Zn) between concentrations in the environment and in the tissue. As final conclusion, the usage of the Asian clam was validated as biomonitor tool in short term exposure to acid mine drainage, and, as early warning responses (72 h), the chosen parameters would be lipid peroxidation and bioaccumulation of a specific set of elements (Fe, Cu, Co, Zn). Ecological water quality levels reached by the passive treatment plant were in agreement with the efficiency of hydrochemical improvements. Graphical abstract: Image 1 Highlights: Asian clam as suitable short term biomonitor through LPO and bioaccumulation. Strong relationship between Fe, Cu, Co and Zn bioaccumulated by the clam and effluents. Low BCF values found for the extreme acid polymetallic environment. Treated effluents acquired the water quality enough for living conditions.